Improvement in Quality of Life after Laparoscopic or Robotic-assisted Sacrocolpopexy with a Single Anterior Mesh in Patients with Pelvic Organ Prolapse: A Retrospective Analysis from a Single Institution - Riyo Kinouchi; Kanako Yoshida; Takako Kawakita; Toshiyuki Yasui; Takeshi Iwasa; Takeshi Kato (Wolters Kluwer Medknow Publications, 2024)
Objectives: Pelvic organ prolapse (POP) is a significant health-care problem for older women. We have treated POP surgically using laparoscopic sacrocolpopexy (LSC) or robotic-assisted sacrocolpopexy (RSC). The original LSC and RSC procedures were done with anterior and posterior meshes; however, the use of the single mesh procedure is increasing because of its simplicity and safety. There have been few reports about the change in quality of life (QOL) using the single mesh procedure. Therefore, the present study aimed to retrospectively evaluate the change in QOL by LSC and RSC using a single anterior mesh for women without posterior compartment prolapse. Materials and Methods: We performed LSC or RSC using a single anterior mesh in 52 patients who had POP without posterior vaginal wall prolapse between August 2018 and October 2022. We assessed the QOL before and after surgery using prolapse-QOL (P-QOL) questionnaires. Results: All patients who received LSC or RSC with a single anterior mesh left the hospital as scheduled without severe perioperative complications. There were no instances of wound infection or vaginal mesh extrusion. The recovery rate of questionnaires was 63.5% (33/52). All QOL score domains improved significantly, and there were no questionnaire parameters that worsened. Conclusion: LSC or RSC using only a single anterior mesh improves P-QOL with a low incidence of surgical complications for POP patients who did not have posterior vaginal wall prolapse. LSC or RSC with a single anterior mesh may be a prospective new procedure for POP.